"Untying the Knots of the Yoke": Yom Kippur and an Agricultural Allusion to Jubilee in Isaiah 58:6 - Kantor, Benjamin (The catholic biblical quarterly, 2023)
A number of scholars have identified allusions to the Jubilee Year found in Isaiah 58. Among these are the trumpet imagery of v. 1 (cf. Lev 25:9) and the self-affliction in vv. 3 and 5 (cf. Lev 16:31). While Jubilee allusions have also been seen in v. 6, which describes the release of slaves alongside imagery of breaking the yoke, I claim here that not all of the allusions to Jubilee in Isa 58:6 have been identified. Though most commentators see the yoke merely as a metaphor for subjugation, there is actually something deeper and more profound going on. The agricultural imagery, when understood rightly in its ancient philological and cultural context, is actually calling to mind the anticipation of the first rainfall that would have accompanied a Yom Kippur (Day of Atonement) on which the Jubilee would be announced. The ancient farmer, who would have been anxious to plow the fields at the right time and avoid potential loss, is called to refrain from plowing and to respect the Jubilee legislation to let the land lie fallow. This serves as a metaphor to call those in society, who regard personal gain as more important than having compassion for their fellow human beings, to repent and embrace the commandments of Yhwh.